Molecular characterization and protective efficacy of vacuolar protein sorting 29 from Eimeria tenella - Shi, Tuan-yuan; Li, Tian-en; Hao, Yun; Sun, Hong-chao; Fu, Yuan; Yan, Wen-chao; Hao, Li-li (Frontiers in Cellular and Infection Microbiology, 2023)
Vacuolar protein sorting 29 (VPS29) is a core component of the retromer-retriever complex and is essential for recycling numerous cell-surface cargoes from endosomes. However, there are no reports yet on VPS29 of Eimeria spp.. Here, we cloned and prokaryotically expressed a partial sequence of Eimeria tenella VPS29 (EtVPS29). The localization of the VPS29 protein in E. tenella sporozoites and its protective efficacy against E. tenella infection were investigated. An EtVPS29 gene fragment with an ORF reading frame of 549 bp was cloned. The band size of the expressed recombinant protein, rEtVPS29, was approximately 39 kDa and was recognized by the chicken anti-E. tenella positive serum. The results of an immunofluorescence assay for subcellular localization and overexpression showed the EtVPS29 protein to be widely distributed in the cytoplasm of E. tenella sporozoites. Animal protection experiments demonstrated that immunization with rEtVPS29 significantly increased average body weight gain and decreased mean lesion score and oocyst output in chickens. The relative weight gain rate in the rEtVPS29-immunized group was 62.9%, which was significantly higher than that in the unimmunized and challenged group (P < 0.05). The percentage of reduced oocyst output in the rEtVPS29 immunized group was 32.2%, which was significantly higher than that in the challenged control group (P < 0.05). The Anticoccidial index of the rEtVPS29-immunized group was 144.2. Serum ELISA also showed that rEtVPS29 immunization induced high levels of specific antibodies in chickens. These results suggest that rEtVPS29 can induce a specific immune response and is a potential candidate for the development of novel vaccines against E. tenella infections in chickens.